High temperature shape memory poly(amide-imide)s with strong mechanical robustness. Issue 35 (19th August 2022) - Lei, Xingfeng; Xiong, Guo; Xiao, Yuyang; Huang, Tianhao; Xin, Xiangze; Xue, Shuyu; Zhang, Qiuyu
Abstract : Shape memory poly(amide-imide)s with strong mechanical robustness, outstanding heat resistance and low water uptake were fabricated. Abstract : Shape memory polymers (SMPs) show tremendous application prospect in various fields owing to their stimuli responsiveness. However, their application in the high value-added aerospace industry still remains a great challenge, since it is problematic to engineer SMPs with both ideal shape memory properties and high heat resistance as well as outstanding mechanical strength. Herein, by incorporating amide hydrogen bonding interactions into a robust imide polymer backbone, a series of poly(amide-imide) hybridization networks have been fabricated, showcasing superior shape memory behavior together with impressive thermal stability and high mechanical strength, with a T g above 300 °C and a tensile strength up to 108.3 MPa. Among all polymers, m -3FPAI exhibits outstanding heat resistance, high mechanical strength, low moisture sensitivity, excellent shape memory property and prominent multiple shape memory tolerance. After six consecutive cycles, a R f still above 98.5% with a R r ranging from 97.8% to 100% was observed, making m -3FPAI a promising candidate to be used in aerospace application.